WINNICOTT AND HELPLESSNESS: DEVELOPMENTAL THEORY, RELIGION, AND PERSONAL LIFE. (October 2014) - LAMOTHE, RYAN
<x xml:space="preserve">Abstract</x> The author examines Winnicott's theory of development from the perspective of existential helplessness, arguing that (a) his views illuminate healthy (and unhealthy) aspects of religion, and (b) express his stance toward the helplessness of dying and death. The author contends that Winnicott understood the infant's psychic growth in relation to the reality of existential helplessness and absolute dependency. Four interrelated, dynamic paradoxes embedded in Winnicott's developmental perspective are discussed, and these paradoxes are seen as frameworks to depict his notions of ego, transitional objects, and true/false selves. The author posits that religion, which Winnicott included under the rubric of transitional phenomena, can be understood in relation to existential helplessness and can be assessed in terms of the degree to which these paradoxes are dynamic.